(untitled) (Iraqi Journal of Medical Sciences, 2009)
Background: The testicular artery arises from aorta below the level of renal arteries, most commonly at the level of L2 vertebra. Variations in the site of origin of the testicular artery may be accounted; it may arise from anomalous origin rather than aorta, or may originate from aorta higher than L2 level or arises from the main renal artery or accessory one. Objectives: study the sites of origin of testicular artery and its clinical importance. Materials & Methods: study the origins of 40 testicular arteries, in both sides of 20 male cadavers in the anatomical laboratory prepared and embalmed for teaching purposes in the medical college. Examine both sides to see the possible origins of the testicular arteries either from aorta or from somewhere else. Results: During dissection of 20 male cadavers, examining 40 testicular arteries on both sides, a different site of origin of the testicular artery was encountered. The right testicular artery was found originated from the right main renal artery. On the other hand, the left testicular artery was found originated from the left accessory renal artery in two cases out of twenty. In the other 17 cases, all the testicular arteries whether right or left were originated from abdominal aorta. Discussion: Variation in the renal and gonadal vasculature has been known since early days of human autopsy. The anomalous origin of testicular artery from accessory renal vessel has important clinical implications, since any surgical intervention with the kidney, during transplantation for example, may lead erroneously to injury of the anomalous testicular artery leading to atrophy of the male gonad. Conclusion: • Testicular artery may originate from anomalous origin rather than aorta. • The anomalous testicular artery is the aberrant one, and no more accessory artery present. • The encountered anomalous origin may comprise a potential risk of bleeding from injured artery during surgery. Keywords: accessory renal arteries, testicular artery, vascular variation.